2020
DOI: 10.1186/s12933-020-01185-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating proprotein convertase subtilisin/kexin type 9 levels and the risk of incident type 2 diabetes in subjects with prediabetes: a population-based cohort study

Abstract: Background Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates cholesterol metabolism by targeting the low-density lipoprotein receptor. Recent studies have shown that circulating PCSK9 is associated with glucose homeostasis and insulin resistance. The aim of this study was to examine the association of circulating PCSK9 levels and risk for the development of type 2 diabetes in individuals with prediabetes. Methods A population-based pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…age, prediabetes, metabolic syndrome) were at an even increased risk [ 19 ]. A Chinese study reported on the association between elevated circulating PCSK9 levels and an increased risk for T2D in women with prediabetes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…age, prediabetes, metabolic syndrome) were at an even increased risk [ 19 ]. A Chinese study reported on the association between elevated circulating PCSK9 levels and an increased risk for T2D in women with prediabetes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size of 300 was evaluated according to a GDM prevalence of 11.91% in China ( 6 ). Referring to a recent study, the mean (SD) of PCSK9 in healthy populations was 283.68 (97.09) ng/ml ( 12 ). In our study, to detect a 50-ng/ml difference in PCSK9 values with a significance level of 0.05 between two groups, the power was 83.6% (α = 0.05).…”
Section: Methodsmentioning
confidence: 93%
“…Previous data observed that PCSK9 levels were increased in type 2 diabetes mellitus/metabolic syndrome patients and positive correlations of PCSK9 levels with LDL, fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c), fasting insulin, and insulin resistance ( 10 , 11 ). Moreover, a recent population-based longitudinal study observed a positive association between serum PCSK9 levels and the incidence of T2DM in the prediabetic populations ( 12 ). In contrast, evidence from an animal study indicated that PCSK9 deficiency reduced insulin secretion and promoted glucose intolerance ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have read the article with great interest by Shi et al on the relationship of circulating proprotein convertase subtilisin/kexin type 9 (PCSK9) concentration with the risk of incident type 2 diabetes mellitus (T2DM) in prediabetic Chinese population [ 1 ]. They concluded that elevated PCSK9 levels were associated with an increased incidence of T2DM in female individuals with prediabetes (pre-DM).…”
mentioning
confidence: 99%
“…Interestingly, Shi et al found a positive relationship with elevated baseline circulating PCSK9 levels and incidence of T2DM in female population with pre-DM during 3.1 years follow-up, which was the first study to undertake a longitudinal analysis of circulating PCSK9 concentration and the development of T2DM in prediabetic individuals [ 1 ]. Although their finding provided an additional information on the association with circulating PCSK9 concentration and the incident risk of new-onset T2DM, there were several issues might be worth deliberating before making a conclusion.…”
mentioning
confidence: 99%